Next-Generation Disinfection: The Role Of UV-C, Hydrogen Peroxide Vapor, And Cold Plasma In Modern Hospitals (The Review of Diabetic Studies, 2024)
Background: Healthcare-associated infections remain a leading cause of morbidity, mortality, and excess costs worldwide, driven by environmental reservoirs and the limitations of manual cleaning in achieving reliable high-level surface disinfection. Next-generation no-touch technologies have emerged to address persistent contamination by multidrug-resistant organisms and spores that withstand conventional methods.​Methods: This narrative review synthesizes evidence from experimental, quasi-experimental, and economic studies evaluating UV-C, HPV, and CAP in hospital settings. Key domains include mechanisms of action, device configurations, log reductions on pathogens, clinical impact on healthcare-associated infections, operational constraints, costs, and future AI- and IoT-enabled innovations.​Results: UV-C systems achieve rapid 3–6 log10 reductions in vegetative bacteria and some spores, with adjunct use associated with approximately 19–30% reductions in selected healthcare-associated infections and notable cost savings. HPV demonstrates superior sporicidal activity and up to 64–80% reductions in multidrug-resistant organism acquisition, albeit with longer cycle times and higher resource demands. CAP offers broad-spectrum, residue-free decontamination with 3–6 log10 reductions in biofilms and spores and promising early clinical and economic signals, but remains constrained by scalability and standardization gaps.​Conclusions: Collectively, these technologies provide complementary strengths that can substantially enhance terminal room decontamination, reduce infection risk, and deliver favorable long-term economic returns when integrated with manual cleaning. However, robust multicenter randomized trials, harmonized dosing and safety standards, and implementation frameworks are required before widespread adoption as core components of hospital infection prevention programs.